Addition to Pseudoplagiostomataceae: Pseudoplagiostoma inthanonense sp. nov. from Doi Inthanon National Park, Northern Thailand - Silva, Veenavee S. Hittanadurage; Perera, Rekhani H.; Farias, Antonio R. Gomes De (Phytotaxa, 2023)
Fungi are dominant microorganisms in plant litter, especially in pristine environments. This study collected leaf litter of broadleaf species within Doi Inthanon National Park, Chiang Mai, Thailand. Phylogenetic analyses utilizing DNA sequence data from ITS, LSU, tef1-α, rpb2, and tub2 regions and morphological characteristics revealed a new species, Pseudoplagiostoma inthanonense (Pseudoplagiostomataceae). The phylogeny and morphology of this novel species are thoroughly described and supported with detailed illustrations. Pseudoplagiostoma inthanonense is characterized by the shape and size of the conidiogenous cell and spore size. The discovery of P. inthanonense confirms that Pseudoplagiostoma consists of pathogenic, endophytic, and saprobic life forms while creating new research opportunities on potential lifestyle changes of Pseudoplagiostoma species.